2021
DOI: 10.1051/e3sconf/202128702015
|View full text |Cite
|
Sign up to set email alerts
|

Viscosity and Ionic Conductivity of Imidazolium based Ionic Liquids bearing Triiodide Anion

Abstract: In the electrolyte application for dye sensitized solar cells, utilization of ionic liquids is getting the highlights to replace volatile organic solvent thanks to their low volatility, thermal and electrochemical stability. The iodide/triiodide redox electrolyte is the preferred choice for this application, hence numerous iodide-based ionic liquids have been explored and reported. On the contrary, the transport properties of triiodide based ionic liquid is often lack of reporting despite of having an equal in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…This is in accord with the study reported in [12] where the incorporation of nitratebased ILs into the Nafion™ membrane has resulted in a greater conductivity of the membrane compared to the usage of formate-based ILs. The variation in length of the alkyl chain attached to the imidazolium-based showed that the longer alkyl chain caused the ionic conductivity to be lower as it induced greater intermolecular attractions and impedes ion mobility as reported in [18,[23][24][25][26]. The phosphonium and boron-based ILs showed significantly lower conductivities compared to the imidazolium and ammonium-based ILs.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…This is in accord with the study reported in [12] where the incorporation of nitratebased ILs into the Nafion™ membrane has resulted in a greater conductivity of the membrane compared to the usage of formate-based ILs. The variation in length of the alkyl chain attached to the imidazolium-based showed that the longer alkyl chain caused the ionic conductivity to be lower as it induced greater intermolecular attractions and impedes ion mobility as reported in [18,[23][24][25][26]. The phosphonium and boron-based ILs showed significantly lower conductivities compared to the imidazolium and ammonium-based ILs.…”
Section: Resultsmentioning
confidence: 84%
“…Apart from that, the length of the alkyl chain of the imidazolium was also varied. Based on the predicted conductivities, the variation of the anion has a greater effect on the ionic conductivity of the resulting ILs [18,23]. The combination of nitrate anion followed by trifluoromethanesulfonate with all cations has resulted in the highest conductivity compared to other anions.…”
Section: Resultsmentioning
confidence: 99%